Manfaat Daun Kelor dalam Sains dan Al-Qur'an - Musyarofah, Atiqatul (Es-Syajar:Journal of Islam, Science and Technology Integration, 2025)
Moringa oleifera leaves are renowned for their immense benefits, both from a scientific perspective and in Islamic teachings. Scientifically, these leaves are rich in active compounds, including vitamins A, B, and C, as well as minerals such as calcium, potassium, and iron. Scientific research highlights their antioxidant, anti-inflammatory, and antimicrobial properties, which contribute towards treating a variety of health conditions. Moringa leaves are also known to effectively lower blood sugar levels, enhance brain function, and reduce cancer risks. From the Quranic perspective, Moringa leaves are regarded as a blessed plant with numerous health benefits. This is reflected in Surah Al-Fath (48:29) and Surah Qaf (50:9), which underscore the importance of plants in human life and their health benefits. Furthermore, hadiths refer to Moringa as a plant that offers blessings and health benefits to humankind. With both scientific evidence and religious teachings supporting the benefits of Moringa leaves, they can be utilized as a nutritious and effective natural remedy. Further research and the application of Moringa in medical and spiritual practices can have a significant positive impact on human health